• Matéria: Matemática
  • Autor: monteiromarialuiza78
  • Perguntado 4 anos atrás

2 x [(5 – 2) x (3 + 2 x 7)] – 2 =

Respostas

respondido por: LuizHenrique1314
1

Resposta:

100

Explicação passo-a-passo:

2 · [(5 - 2) · (3 + 2 · 7)] - 2 =

2 · [(5 - 2) · (3 + 14)] - 2 =

2 · [(3) · (3 + 14)] - 2 =

2 · [3 · (17)] - 2 =

2 · [3 · 17] - 2 =

2 · [51] - 2 =

2 · 51 - 2 =

102 - 2 =

100

respondido por: KatiaBellato
1

Resposta:

208

Explicação passo-a-passo:

2 x [(5 - 2) x (3 + 2 x 7)] - 2 =

2 x [3 x 35] - 2 =

2 x 105 - 2 =

210 - 2 =

208

Perguntas similares